DESIGN OF LOCAL COMPUTER NETWORKS USING NOVELL NETWARE ON THE PO KRAMAT DJATI SERUA – PARUNG - Sonny Soelaksono; Ir. Setijo Budiutomo Ir. Setijo Budiutomo (Jurnal Sistem Informasi, 1997)
Existence of computers has brought human beings into situations that have neverpreviously imagined. Science world of knowledge, education, services and otherstake advantage of the existence of these seriously. Computer network is one facilitythat can be utilized to carry out all activities with all security computerize.Complement feels, if the existence of these networks are supported with a variety ofsoftware used. Novell is one of the software, which can be used in a variety of needs.By computer network, the completeness of the data can be stored safely and trafficinformation can be going well